Pengaruh media pembelajaran berbasis aplikasi android terhadap motivasi belajar pendidikan agama islam dan budi pekerti bagi siswa SMP Negeri 1 Jatisrono tahun ajaran 2021/2022 - Nurul Latifatul Inayati; Rizki Azra Maulana; Annas Fajar Rohmani (At Turots: Jurnal Pendidikan Islam, 2023)
Learning media is used by every teacher in the educational process at school. Good quality teachers can develop interactive learning media so as to increase student motivation. Researchers have designed an interactive learning media based on an Android application. The purpose of this study is to find out whether the learning media designed by this researcher can influence student learning motivation, especially at SMP Negeri 1 Jatisrono. The method used in this study is a quantitative experimental approach. The sample in this study were students in class VIII D and G of SMP Negeri 1 Jatisrono for the 2021/2022 academic year, who were selected using the random sampling method. Data collection techniques are interviews and tests which are divided into two stages, pretest and posttest. Data analysis techniques used statistical tests using the SPSS application with assumption tests, namely homogeneity tests and normality tests then hypothesis testing using the Mann Whitney test. The results showed that there was a significant change in students' learning motivation after being given treatment in the form of learning media based on android applications.